Mercury Concentrations in Fish Species from Can Gio Mangrove Reserve and Implications for Human Health Risk - Le, Dung Quang; Bui, Thanh-Khiet L. (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Mercury (Hg) exposure in humans primarily occurs through fish consumption, making fish an important indicator of potential health risks. This study represents one of the first efforts to assess Hg levels in edible marine fish from Can Gio Mangrove Reserve (CGMR), Vietnam, providing essential baseline data for evaluating potential health risks to consumers. A total of 75 fish specimens were analyzed for mercury concentrations in their muscle tissue. Hg levels ranged from 0.02 to 0.61 mg.kg-1 dry weight, with an average concentration of 0.16 mg.kg-1 dry weight. Among the species studied, the large-eye croaker (Johnius plagiostoma) had the highest average mercury level (0.19 mg.kg-1 dry weight), followed by Reeve’s croaker (Chrysochir aureus) at 0.14 mg.kg-1, and Cynoglossus bilineatus with the lowest level at 0.12 mg.kg-1. A positive correlation was observed between mercury concentrations and body size in the large-eye croaker (R²= 0.54, P< 0.04). Despite this variation, the mercury levels in all three species were below the Provisional Tolerable Weekly Intake (PTWI) recommended by the Joint FAO/WHO Expert Committee on Food Additives (JECFA). Based on these findings, the study recommends that these fish should not be consumed more than 10 times per month, assuming a meal size of 0.227 kg, to ensure that mercury intake remains within safe limits and does not pose a health risk. The relatively low mercury levels in the fish sampled from CGMR suggest that the ecosystem is not currently a significant source of mercury contamination. However, the study highlights the importance of ongoing monitoring to detect potential changes in mercury levels, particularly in the face of increasing human activities in the region in future.